Basic Income in Uruguay: Political Feasibility and Debates in the Latin American Context (Revista Rupturas, 2025)
This article examines the political and institutional feasibility of Universal Basic Income (ubi) in Uruguay within the Latin American context. Based on research conducted between 2021 and 2022, funded by the Universidad de la República, the study analyzed the perceptions of political, social, and academic actors through focus groups and an elite survey. The results reveal a polarized debate, where UBI’s feasibility faces political, fiscal, and ideological challenges. Although there is no immediate consensus, favorable arguments and spaces for articulation emerge, suggesting the possibility of further discussion in the medium and long term.
Keywords: universal basic income; social protection; Uruguay; public policy; Latin America